A rare case of ovarian torsion in a pregnant patient - Kumari, Swati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Torsion of the ovary is the total or partial rotation of the adnexa around its vascular axis or pedicle. It is an uncommon cause of acute abdominal pain in females, and it is a gynecologic emergency. The majority of the cases present in the pregnant (22.7%) than in non-pregnant (6.1%) women. Diagnostic delay can result in loss of the ovary. This twisting initially obstructs venous flow, which causes engorgement and edema. The engorgement can progress until arterial flow is also compromised, leading to ischemia and infarction. The increased use of ovarian stimulation and assisted reproductive technology has led to an increase in the risk of adnexal torsion, particularly in pregnant women or women with ovarian hyperstimulation syndrome (OHSS). The differential diagnosis of adnexal torsion is particularly difficult in combination with OHSS or pregnancy, as abdominal pain, nausea and vomiting can be presenting symptoms of hyperstimulation or pregnancy as well. Here, we report a case of ovarian torsion occurring in pregnancy in which diagnostic delay occurred due to confusion with OHSS leading to oophorectomy. Fertility conservation may have been possible in case of earlier diagnosis and prompt treatment.